In the Wake of Violence : Image & Social Reform - Jorgensen-Earp, Cheryl R. (Book collections on Project MUSE., 2008)
How acts of violence are rhetorically ""managed"" by social movements: In the Wake of Violence explores the immediate and longer term aftermath of violence committed by independent radicals involved in single-issue movements. Cheryl R. Jorgensen-Earp explores several specific incidents in recent history-the arson of a Vail ski resort by environmentalists, the murder of Dr. John Britton by an antiabortion activist, and the torching of a University of California research laboratory by animal rights activists among them-to discover how the perpetrators of the violence and.